Radioguided localisation of impalpable breast lesions using 99m‐Technetium macroaggregated albumin: Lessons learnt during introduction of a new technique to guide preoperative localisation. Issue 1 (25th December 2013) - Landman, Joanne; Kulawansa, Sagarika; McCarthy, Michael; Troedson, Russell; Phillips, Michael; Tinning, Jill; Taylor, Donna
Abstract Introduction Preoperative wire‐guided localisation (WGL) of impalpable breast lesions is widely used but can be technically difficult. Risks include wire migration, inaccurate placement, and inadequate surgical margins. Research shows that radioguided occult lesion localisation (ROLL) is quicker, easier, and can improve surgical and cosmetic outcomes. An audited introduction of ROLL was conducted to validate the technique as a feasible alternative to WGL. Methods Fifty patients with single impalpable lesions and biopsy proven malignancy or indeterminate histology underwent WGL followed by intralesional radiopharmaceutical injection of 99m‐Technetium macroaggregated albumin. Postprocedural mammography was performed to demonstrate wire position, and scintigraphy to evaluate radiopharmaceutical migration. Lymphoscintigraphy and intraoperative sentinel node biopsy were performed if indicated, followed by lesion localisation and excision using a gamma probe. Specimen imaging was performed, with immediate reexcision for visibly inadequate margins. Results Accurate localisation was achieved in 86% of patients with ROLL compared to 72% with WGL. All lesions were successfully removed, with clear margins in 71.8% of malignant lesions. Reexcision and intraoperative sentinel node localisation rates were equivalent to preaudit figures for WGL. ROLL was easy to perform and problems were infrequent. Inaccurate radiopharmaceutical placement necessitating WGL occurred in four patients. Minor radiopharmaceutical migration was common, but precluded using ROLL in only two cases. Conclusions ROLL is effective, simple, inexpensive, and easily learnt; however, preoperative confirmation of correct radiopharmaceutical placement using mammography and the gamma probe is important to help ensure successful lesion removal. Insertion of a backup hookwire is recommended during the initial introduction of ROLL.